Fluorosurfactants‐Directed Preparation of Homogeneous and Hierarchical‐Porosity CMP Aerogels for Gas Sorption and Oil Cleanup. Issue 1 (28th January 2015) - Du, Ran; Zheng, Zhe; Mao, Nannan; Zhang, Na; Hu, Wenping; Zhang, Jin
Abstract : Homogeneous, hierarchical‐porosity and highly hydrophobic conjugated microporous polymer (CMP) aerogels are facilely prepared assisted by fluorosurfactants. The fluorosurfactants show several roles in controlling the gelation process, modulating pore structures, and raising the hydrophobicity of materials, thus giving rise to aerogels with exceptional gas sorption and oil cleanup performance.